Karakteristik Akustik Ruang Sidang Jurusan Fisika FMIPA-ITS sebagai Ruang Konferensi: Suyatno, Susilo Indrawati - Suyatno Suyatno; Susilo Indrawati Susilo Indrawati (Jurnal Fisika dan Aplikasinya, 2017)
Acoustic parameter value required for conference room is the loudness and clarity of votes received by each participant. To get the quantification of these parameters, the necessary measurements of the distribution of acoustic parameters include SPL, C80, D50, and RT. SPL distribution measurement is done by using the sound source berupawhite noise of loudspeakeryang placed in leadership positions (front) and the receiver (in this case microphones) in the viewing area. As for the measurement of RT, C80 and D50, is done by providing a source of steady sound level of 100 dB or front impulsdi response resources. As the space for meetings (conferences), the space has a dimension of 10 m x 14 m are expected every participant will receive sound directly from the source. From the measurement results, the value of the acoustic parameter space has a different value of SPL between front and rear position reaches more than 8 dB, while the reverberation time parameter values from 1.0 to 1.28 s, C80 by 1–4 dB and D50 is 41–55%. This value meets the prerequisites as a conference room, but the need for improvements to the distribution parameter SPL. For that we need special treatment to the distribution of SPL in order to be equitable. In the end, all participants will feel comfortable when attending meetings or activities performed in that space.